The impact of earnings variability and regulatory measures on income smoothing: Evidence from panel regression - Amina Malik; Haroon Aziz; Buerhan Saiti; Shahab Ud Din (Journal of Central Banking Theory and Practice, 2021)
This study investigates the impact of variability in earnings, stringent regulatory measures and the trend of extending loans while keeping in view deposit ratio on income smoothening practices for a sample of 20 commercial banks listed on the Pakistan Stock Exchange (PSX) from the year 2010 to 2017. The likelihood of smoothing activities is measured through its widely used proxy, i.e. loan loss provisions (LLPs). Moreover, earnings before tax and provisions (EBTP) and loan to deposit ratio (LD) have been incorporated to determine the impact of earnings and loans to deposit ratio on income smoothening. We find that commercial banks are less likely to manage earnings through smoothening practices, which shows that commercial banks adhere to regulatory restrictions. This is further supported by the fact that income smoothing activities decrease as a result of the increase in capital adequacy ratios after the imposition of stringent rules, which exert greater regulatory pressure on banks, whereas the pace of income smoothing increases as a result of an increase in loans to deposit ratio, which reveals that banks take credit risk but manage within the ambit of regulatory restrictions. Based on the findings, we argue that the imposition of regulatory restrictions through the State Bank of Pakistan (SBP) has not only discouraged income smoothening through loan loss provisions but also enhances reporting quality. The results of this study provide useful insights for investors, creditors and stakeholders.
Keywords: G21; B26; C23; 330; income smoothing; earnings variability; regulatory measures; capital adequacy ratio; loan to deposit ratio; Kreditgeschäft; Kreditrisiko; Bilanzpolitik; Basler Akkord; Finanzmarktregulierung; Spezialbank; Pakistan